Analysis of the Impact of Implementing the Independent Curriculum on the Development of Students' Critical Thinking - Pulungan, Hoirina; Maharani, Tia; Sulistyani, Shiwi; Lubis, Inayah Hanum; Harahap, Safinatul Hasanah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
In an effort to improve the quality of education, the implementation of the Merdeka Curriculum is a major concern. Developing learners' critical thinking skills is the main goal of the Merdeka Curriculum. According to critical thinking theory, this ability is needed to face challenges around the world and solve difficult problems. Therefore, this study aims to evaluate the impact of implementing Merdeka Curriculum on students' critical thinking development. The results showed that the implementation of Merdeka Curriculum has a significant effect on students' critical thinking skills, especially in terms of improving their ability to analyze, compile, and assess. However, this study also found several problems encountered in the implementation of the Merdeka Curriculum, such as lack of teacher support and lack of resources. This research is expected to contribute to the development of a more efficient curriculum and the improvement of education quality in Indonesia. The results suggest that teachers and educational institutions should increase support and resources to improve the effectiveness of KM implementation.